Build school competitiveness through the adiwiyata program (best practice) - Andrianopel Andrianopel (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2018)
The low level of concern of the school community towards the environment is a problem that occurs in the SMU 1 District of Luak. The school environment is arid, garbage is everywhere. The toilet is dirty, the walls of the class and the furniture are streaked, and other environmental problems. As a result, the community is less interested in sending their children to this school and choosing another place for their sons and daughters. This happened at least until the beginning of 2014. The problems raised in this paper are: how to build school competitiveness so that it becomes the people's choice. Through the implementation of the Adiwiyata school program, school residents have had a high concern for their environment and cultivated a clean and healthy life so that the face of the school has changed. Physically, schools look clean, green, organized, and fun for all school people. In 2015, the school received an award as a district-level adiwiyata school and in 2016 received the title of a provincial adiwiyata school. At this time, the community has looked at SMPN 1 Luak District as an option. Through the implementation of the Adiwiyata program, it turns out that school competitiveness can be improved.